AB0715 Evaluation of patients with elevated sedimentation and crp levels: attention to non-rheumatological diagnoses!. (23rd January 2014) - Bitik, B.; Tezcan, M. E.; Tufan, A.; Mercan, R.; Kaya, A.; Ozturk, M. A.; Haznedaroglu, S.; Goker, B.
Abstract : Background: Erythrocyte sedimentation rate (ESR) and high C-reactive protein (CRP) are the most commonly used acute phase reactants to detect and follow up disease activity in rheumatology clinics. Besides rheumatic diseases (RD), infections and malignancies are two of the major causes of high ESR and CRP. The diagnosis can be challenging especially in serologically unrevealing patients who have nonspecific clinical findings. These patients often require extensive investigations to identify the condition associated with elevated ESR and CRP levels. Objectives: In this retrospective study we aimed to determine the definitive diagnosis of undiagnosed and untreated patients with high ESR and CRP. Methods: Electronic medical records of patients hospitalized in Rheumatology clinic between January 2010 and May 2011 were retrospectively analysed. Patients demographics, the levels of ESR and CRP on the day of hospitalization and definitive diagnoses were recorded. The definitive diagnoses were divided into three groups: (1) newly diagnosed RD; (2) newly diagnosed non-RD; and (3) flare of RD. Non-RD was than subdivided into infections, malignancies and others. Results: Data were collected on 113 patients (84 female), of whom 32 had a newly diagnosed RD, 39 had non-RD (20 infection, 6 malignancy, 13 others) and 36 had flare of RD. The age, ESR, and hospitalization duration did not differ significantly between the groups. CRP was significantly higher in the infection subgroup than in the RD group (p=0.005). CRP level did not differ significantly between the RD group and malignancy subgroup (p=0.055)[Table 1 ]. The most frequent diagnoses were temporal arteritis and/or polymyalgia rheumatica and seronegative rheumatoid arthritis, respectively in the RD group. Non-RD were infections, malignancies, gastrointestinal diseases and the other causes, respectively [Table 2 ]. Conclusions: In this study, patients with nonspecific clinical findings and high acute phase reactants were more likely to have non-RD compared to newly diagnosed RD. CRP level was significantly higher in infectious diseases than in newly diagnosed RD. Pyhsicians should keep in mind the probability of an infection or a malignancy in patients with high acute phase reactants but no specific clinical findings suggestive of RD. Disclosure of Interest: None Declared